Successful Community Empowerment Strategies Related to Environmental Issues in Indonesia - Syahadat, Ray March; Putra, Rizal Ichsan Syah; Putra, Priambudi Trie (Indonesian Green Technology Journal, 2026)
Several community empowerment programs related to environmental topics have been reported in Indonesia. Various programs have been carried out. Several studies report the success and failure of these programs. This article aims to summarize the strategies reported to support the success of the future empowerment program. This literature review can contribute to the field of environmental science, community empowerment, and other relevant studies. The success strategy topic was chosen based on the results of a bibliometric analysis using Harzing's Publish or Perish application and VOSviewer. A total of 20 relevant articles were then selected through Google Scholar and analyzed descriptively. The results show that 10 strategies are needed to support the success of community empowerment programs addressing environmental issues